Wawancara dengan Taring Padi: Kepeloporan, Kreativitas, Simbol, dan Peristiwa Documenta Fifteen - Heronimus Heron; Min Seong Kim (Sanata Dharma University, 2023)
A work by the Indonesian artist collective Taring Padi titled People’s Justice caused great controversy during the fifteenth edition of Documenta, which took place in Kassel in the year 2022. While discussions over the Documenta incident were still ongoing, on 19 September 2022, we were able to meet eight of the members of Taring Padi in Yogyakarta, Indonesia, to hear their thoughts on the controversy as well as gain insight into their creative process and political orientation. We publish the interview in full in Retorik with the permission of Taring Padi.